1990
DOI: 10.2307/3325258
|View full text |Cite
|
Sign up to set email alerts
|

Superfund Expenditures and Cleanup Priorities: Distributive Politics or the Public Interest?

Abstract: Using data on all final National Priorities List (NPL) sites, this study employs an integrated model of distributive and public interest politics to determine whether the overall pace of cleanup efforts and funding of the 8.5 billion Superfund program over the past eight years reflects self‐interested congressional influence or public interest objectives. Despite the fact that both EPA and Congress have substantial incentives to promote the Superfund program, the results indicate that once a site is on the fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 17 publications
0
31
0
1
Order By: Relevance
“…20 On a quite different U.S. issue, Hoagland and Farrow (1996) likewise found that the planning decisions made by the secretary of the Interior concerning the sale of leases for offshore gas and oil drilling depended not only on political variables but also on the estimated net social value attached to the various sites. And in a third case, Hird (1990), in a study of Superfund expenditures to clean up hazardous waste sites in the United States, found that the chief determinant of the pace and funding of cleanup at particular sites was the site's hazard rankinga measure of its public health risk-with only more modest influence from interested legislators.…”
Section: Empirical Studies Of the Political Economy Of Environmental mentioning
confidence: 99%
“…20 On a quite different U.S. issue, Hoagland and Farrow (1996) likewise found that the planning decisions made by the secretary of the Interior concerning the sale of leases for offshore gas and oil drilling depended not only on political variables but also on the estimated net social value attached to the various sites. And in a third case, Hird (1990), in a study of Superfund expenditures to clean up hazardous waste sites in the United States, found that the chief determinant of the pace and funding of cleanup at particular sites was the site's hazard rankinga measure of its public health risk-with only more modest influence from interested legislators.…”
Section: Empirical Studies Of the Political Economy Of Environmental mentioning
confidence: 99%
“…That is, rather than counties with a high poverty rate, for example, being less politically active and hence having higher levels of pollution in their community in fact the higher pollution levels may cause wealthier people to leave the community and hence the remaining population has a higher poverty level. Since our primary focus 9 See for example Hird (1990), Hamilton (1993 and, Gray and Deily (1996), Helland (1998) and Arora and Cason (1999) among others, who find that local communities can be important in determining the level of pollution emitted from a facility. 10 The poverty and minority percentages are not available for all years and we linearly interpolate the missing values.…”
Section: Control Variablesmentioning
confidence: 99%
“…When local industries pollute lawmakers and regulators must balance two primary concerns: economic prosperity and the environment. The role of political pressure is well-documented in environmental policy (Oates (2001), Magat, et al (1986), Hird (1990)). In general the theory suggests that local control is at least as efficient as any other political jurisdiction in dealing with local pollution simply because the median voter receives both the costs and benefits of the policy.…”
Section: Introductionmentioning
confidence: 99%
“…Weingast and Moran (1983), McCubbins et al (1987), Gilligan et al (1989), andHelland (1999) all present evidence for legislative effects on agency decision making, and as Olson (1995) has found that no single theory appears to explain the entirety of agency decision making, this analysis also includes variables proxying for the potential effect of legislative pressure on FERC decision making. Empirical evidence to support inclusion of legislative variables when attempting to explain regulatory delay in particular comes from Hird (1990), who discovered that legislators can hasten a Superfund site's transition by the EPA from proposed to final NPL status. We would expect that the more environmentally friendly the disposition of Congress, the more quickly relicensing projects are completed.…”
Section: Hypothesismentioning
confidence: 99%